PERMAINAN TRADISIONAL GOTAH UNTUK PENGEMBANGAN ANAK USIA DINI - Saparina Saparina; Aunurrahman Aunurrahman; Lukmanulhakim Lukmanulhakim (Jurnal Visi Ilmu Pendidikan, 2022)
Abstract This study aims to describe the potential of traditional gotah games for early childhood development in Desa Beringin, Kabupaten Kapuas Hulu. The research method used is descriptive method in the form of qualitative research. Sources of data in this study were the community, PAUD teachers and children aged 4-6 years in Desa Beringin, Kabupaten Kapuas Hulu. Data collection techniques used in this study were observation, interviews, and documentation. The results showed that: 1. Gotah traditional games in developing the potential of early childhood morals contained the ability to behave well, self-development of good behavior, sportsmanship, respect and honesty, 2. Gotah traditional games in the aspect of potential early childhood gross motor skills contained in gross motor skills and fine motor skills.Thus, the traditional game guide of gotah has the potential to develop early childhood aspects in Desa Beringin, Kabupaten Kapuas Hulu.     Keywords: Gotah Traditional Games and Early Childhood Development